EFFECTS OF SPACINGS AND BUTACHLOR LEVELS ON WEED CONTROL, GROWTH AND YIELD OF NERICA 1 RICE (ORYZA SATIVA X ORYZA GLABERRIMA L.) IN NORTHERN GUINEA SAVANNAH - Kasim, Hassan; Musa, Ibrahim; Muhamman, Mustapha Alhaji (Journal of Agricultural Sciences (Belgrade), 2017)
Abstract: Poor agronomic practices coupled with herbicide mismanagement influences crop performance, yield, weeds infestation and environmental hazards. Thus, Field experiments were carried out to investigate the effect of spacing and reduced levels of Butachor on weed control and yield of NERICA 1 rice (Oryza sativa L. x Oryza glaberrima L). The experiments were conducted in the 2011 rainy season at the Teaching and Research Farm of the Department of Crop Production and Horticulture, Modibbo Adama University of Technology Yola, and Lake Gerio, Yola in 2012 dry season. Yola is located between Latitude 9o14′ N and Longitude 12o28′ E in the Northern Guinea Savanna Ecological Zone of Nigeria. Treatments consisted of four spacings (20 cm x 20 cm, 17 cm x 17 cm, 14 cm x 14 cm and 11 cm x 11 cm) and four Butachlor levels (3, 2, 1, and 0 kg ha‑1 a.i.). The experiments were laid out in a split plot design with spacing assign to the main plot and Butachlor levels assign to the sub-plot and were replicated three times. Date were taken on percentage establishment, number of leaves per plant, general weed cover, panicle length and grain yield per hectare. Data generated were subjected to analysis of variance. Means showing significant F – test were separated using LSD. Results obtained showed that Butachlor at 1 kg ha‑1 with 14 cm x 14 cm spacing gave the highest grain yield of 1441 kg ha‑1 and maximum weed control. It is therefore, recommended for adoption by farmers in Yola and similar environment.
Keywords: Yield; NERICA; Butachlor; Spacing; weeds